2013
DOI: 10.1016/j.ajhg.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in MED12 Cause X-Linked Ohdo Syndrome

Abstract: Ohdo syndrome comprises a heterogeneous group of disorders characterized by intellectual disability (ID) and typical facial features, including blepharophimosis. Clinically, these blepharophimosis-ID syndromes have been classified in five distinct subgroups, including the Maat-Kievit-Brunner (MKB) type, which, in contrast to the others, is characterized by X-linked inheritance and facial coarsening at older age. We performed exome sequencing in two families, each with two affected males with Ohdo syndrome MKB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 34 publications
3
88
0
1
Order By: Relevance
“…Missense mutations of MED12 are associated with X-linked genetic syndromes [103][104][105]. Somatic mutations have been described in many solid tumors, including, hormone-associated cancers (prostate and adrenocortical carcinoma) [106,107], breast [108], uterine tumors [109].…”
Section: Med12 Mutationsmentioning
confidence: 99%
“…Missense mutations of MED12 are associated with X-linked genetic syndromes [103][104][105]. Somatic mutations have been described in many solid tumors, including, hormone-associated cancers (prostate and adrenocortical carcinoma) [106,107], breast [108], uterine tumors [109].…”
Section: Med12 Mutationsmentioning
confidence: 99%
“…4 Although in these cases, the individual effect of increased MED13L dosage cannot be determined because of the involvement of several genes, it further underlines a possible gene dosage effect. MED13L is only one component of the mediator complex linked to human disease: (i) MED12 gene variants cause Lujan-Fryns syndrome (MIM #309520), 25 Ohdo syndrome (MIM #300895), 26 Opitz-Kaveggia syndrome (MIM #305450), 27 and profound ID that in contrast to the aforementioned syndromes resulted in affected female carriers and truncation of the MED12 protein, 28 (ii) a recurrent homozygous MED17 missense variant has been linked to postnatal progressive microcephaly with seizures and brain atrophy (MIM #613668), 29 (iii) a homozygous MED23 variant causes autosomal recessive nonsyndromic ID (MIM #614249), 30 (iv) a homozygous MED25 variant causes autosomal recessive adult onset axonal Charcot-Marie-Tooth neuropathy (CMT2B2, MIM #605589) 31 and (v) a truncation of CDK19 caused by a chromosome inversion is associated with bilateral congenital retinal folds, microcephaly, and mild ID (MIM #614720). 32 We observe that the MED13L phenotype displays similarities to OpitzKaveggia syndrome, along with key differences (see Table 3).…”
Section: Exon 10mentioning
confidence: 99%
“…MED12, a component of the Mediator kinase submodule, is encoded on the X chromosome, and missense mutations are associated with a variety of X-linked disorders (17)(18)(19). Developmental signaling pathways and transcription factors converge on MED12, which acts as a transcriptional hub required to coordinate development (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The kinase submodule, containing MED12, MED13, CDK8, and Cyclin C (12), can repress transcription through allosteric inhibition of RNA Pol II binding to the core submodule (13) but can also activate transcription by promoting Pol II recruitment to target genes via specific transcription factors (14). We previously demonstrated that cardiac MED13 regulates systemic energy homeostasis through signaling to extracardiac tissues (15,16), but the roles of the other kinase components in the heart have not been investigated.MED12, a component of the Mediator kinase submodule, is encoded on the X chromosome, and missense mutations are associated with a variety of X-linked disorders (17)(18)(19). Developmental signaling pathways and transcription factors converge on MED12, which acts as a transcriptional hub required to coordinate development (20)(21)(22)(23).…”
mentioning
confidence: 99%